2019
DOI: 10.1002/ima.22366
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity differences in brain networks from childhood to youth

Abstract: Examining while using the resting‐state functional magnetic resonance imaging (rs‐fMRI) of brain development in terms of functional connectivity between childhood and adulthood in healthy subjects gives important information. In this study, it was aimed to examine the changes in functional networks between healthy age groups by using rs‐fMRI for prepuberty (childhood), puberty, and adolescence by examining changes within and between networks. The rs‐fMRI data in this study were obtained from the New York Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(285 reference statements)
0
1
0
Order By: Relevance
“…Sleep problems on the other hand can negatively affect these domains and are also likely to have an impact on cognition, physical health, and academic performance 3 . Due to rapid developmental changes (e.g., cortical reorganization processes in the maturing brain), children and adolescents are at heightened risk for the onset of sleep and mental health issues 4 , 5 . In fact, it has been shown that sleeping problems in children and adolescents are linked to behavioral (e.g., self-regulation, conduct, attention) and emotional (e.g., depression, anxiety, stress) problems 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problems on the other hand can negatively affect these domains and are also likely to have an impact on cognition, physical health, and academic performance 3 . Due to rapid developmental changes (e.g., cortical reorganization processes in the maturing brain), children and adolescents are at heightened risk for the onset of sleep and mental health issues 4 , 5 . In fact, it has been shown that sleeping problems in children and adolescents are linked to behavioral (e.g., self-regulation, conduct, attention) and emotional (e.g., depression, anxiety, stress) problems 6 8 .…”
Section: Introductionmentioning
confidence: 99%